Radiological Risk to Inhalation of Thoron Gas from Medical Materials Samples Derived from Medical Plants in Iraq - Abojassim, A. A.; Lawi, D. J.; Hassan, A. B. (National Research and Innovation Agency, 2024)
Pollution by thoron is one of the factors that is harmful to human health. Medical materials, especially those derived from plants, have natural ingredients which are a major source of natural radioactivity, thoron being one of them. Therefore, the presence of harmful radioactivity in these materials is a matter of concern. This study determined the concentrations of thoron (220Rn or radon-220) from 70 samples of medical materials derived from medical plants using a CR-39 detector. Samples are drugs (solid), skin creams, herbs, toothpaste, drugs (liquid), and cosmetic products found in Iraqi pharmacies. Also, radiological risks such as Annual Effective Dose (AED), Excessive Lifetime Cancer Risk (ELCR), and Lung Cancer Case (LCC) due to inhalation of thoron from medical materials samples in pharmacies were calculated. The results show that the results of the thoron concentrations in the samples of medical materials ranged from 1.02 Bq/m3 to 74.53 Bq/m3, with an average value of 18.21 ± 2.00 Bq/m3. The range values of AED, ELCR (×10-3) and LCC (×10-6) were 0.01-0.588 mSv/y, 0.04-2.36, and 0.18-10.58, respectively. It was als found that the thoron concentrations in samples of the present study vary from a minimum of 12.82 Bq/m3 in cosmetic products samples to a maximum of 30.29 Bq/m3 in herbs samples. Nonetheless, all thoron and radiological risk values were lower than the acceptable world limit (thoron = 200-300 Bq/m3 by ICRP and AED = 1.1-4.4 mSv/y by UNSCEAR).